2012
DOI: 10.1523/jneurosci.2215-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Autism-Associated Mutations in ProSAP2/Shank3 Impair Synaptic Transmission and Neurexin–Neuroligin-Mediated Transsynaptic Signaling

Abstract: Mutations in several postsynaptic proteins have recently been implicated in the molecular pathogenesis of autism and autism spectrum disorders (ASDs), including Neuroligins, Neurexins, and members of the ProSAP/Shank family, thereby suggesting that these genetic forms of autism may share common synaptic mechanisms. Initial studies of ASD-associated mutations in ProSAP2/Shank3 support a role for this protein in glutamate receptor function and spine morphology, but these synaptic phenotypes are not universally p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
163
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(172 citation statements)
references
References 70 publications
(124 reference statements)
7
163
0
Order By: Relevance
“…In fact, another study includes a similar deletion, which excised exon 4 to 7 (Shank3 e4 -7 ), although the majority of the results from that study refer to a downstream deletion of exons 13-16, resulting in the knockout of many shorter isoforms not affected in the other studies [72]. In addition, two recent studies have used gene expression in cultured hippocampal neurons to look at the subcellular mechanisms of Shank3, and the effect of point mutations in the ankyrin repeats domain associated with autism ( [14,73]; tables 3 and 4).…”
Section: (C) Shank3mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, another study includes a similar deletion, which excised exon 4 to 7 (Shank3 e4 -7 ), although the majority of the results from that study refer to a downstream deletion of exons 13-16, resulting in the knockout of many shorter isoforms not affected in the other studies [72]. In addition, two recent studies have used gene expression in cultured hippocampal neurons to look at the subcellular mechanisms of Shank3, and the effect of point mutations in the ankyrin repeats domain associated with autism ( [14,73]; tables 3 and 4).…”
Section: (C) Shank3mentioning
confidence: 99%
“…The Shank proteins bind neuroligins, suggesting that understanding the functional roles of this interaction may give insights into the underlying pathology of at least some forms of ASD. In this context, an intriguing recent study has shown that the overexpression of Shank3 results in alterations not just in postsynaptic function but also in presynaptic function and that this effect is mediated by the interaction between neuroligins and neurexins [73]. The introduction of ASD mutations in Shank3 (R87C, R375C, Q396R and InsG) impaired both pre-and postsynaptic function at glutamatergic synapses.…”
Section: Towards a Unifying Hypothesis Formentioning
confidence: 99%
“…They are considered central regulators of postsynaptic function, interacting with a large number of postsynaptic molecules including glutamate receptors, structural proteins, and the actin cytoskeleton (Boeckers et al, 2002;Kreienkamp, 2008). Shank3 also interacts with the C-terminal tails of Neuroligin 1 and 3 (Meyer et al, 2004) and thus couples changes in postsynaptic reception with presynaptic neurotransmitter release via the trans-synaptic Neurexin/Neuroligin complex (Arons et al, 2012). Both knock-down of endogenous Shank3 and overexpression of autism spectrum disorder (ASD)-associated Shank3 variants interfere with trans-synaptic signaling, indicating that presynaptic and postsynaptic coupling are likely targeted by ASD mutations (Kumar and Christian, 2009;Miles, 2011;Arons et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Shank3 also interacts with the C-terminal tails of Neuroligin 1 and 3 (Meyer et al, 2004) and thus couples changes in postsynaptic reception with presynaptic neurotransmitter release via the trans-synaptic Neurexin/Neuroligin complex (Arons et al, 2012). Both knock-down of endogenous Shank3 and overexpression of autism spectrum disorder (ASD)-associated Shank3 variants interfere with trans-synaptic signaling, indicating that presynaptic and postsynaptic coupling are likely targeted by ASD mutations (Kumar and Christian, 2009;Miles, 2011;Arons et al, 2012). Shank3-deficient mice show deficits in glutamatergic excitatory synaptic transmission, decreased LTP expression, and altered social interaction and anxietyrelated behaviors (Bozdagi et al, 2010;Kouser et al, 2013;Duffney et al, 2015;Lee et al, 2015;Speed et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation